2016
DOI: 10.1002/14651858.cd010222.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant treatment for subsegmental pulmonary embolism

Abstract: Editorial group: Cochrane Vascular Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 2, 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Incidental and isolated subsegmental PE should generally be managed in the same manner as symptomatic and non-subsegmental PE [43]. This hypothesis, however, should be assessed in prospective clinical trials [44]. By contrast, patients diagnosed with acute symptomatic PE, concomitant DVT was significantly associated with an increased risk of death within 30 days of PE diagnosis [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…Incidental and isolated subsegmental PE should generally be managed in the same manner as symptomatic and non-subsegmental PE [43]. This hypothesis, however, should be assessed in prospective clinical trials [44]. By contrast, patients diagnosed with acute symptomatic PE, concomitant DVT was significantly associated with an increased risk of death within 30 days of PE diagnosis [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of detecting subsegmental PE (SSPE) has been an ongoing debate for more than a decade[ 21 ]. An isolated SSPE could be a symptom of a thrombotic state, and may require treatment[ 22 ]. Recently Mehta et al[ 23 ] have shown that withholding anticoagulation in patients with a single SSPE and negative bilateral lower extremity venous duplex ultrasound exams was a safe and effective strategy.…”
Section: Treatment For Subsegmental Pe Remains a Conundrummentioning
confidence: 99%
“…Additionally, the paucity of dyspnea despite profound hypoxemia in COVID-19 makes it difficult to identify a high-risk patient clinically. This clinical picture mirrors patients with peripheral subsegmental pulmonary emboli who show minimal or no symptoms that precludes early diagnosis, 20 but risk rapid decline especially with endotracheal intubation.…”
Section: Clinical Trajectory In Severe Covid-19 ‘Pneumonia’ Reflects mentioning
confidence: 62%